2018
DOI: 10.1016/j.rser.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and performance of hybrid redox flow batteries with zinc negative electrodes for energy storage

Abstract: Zinc negative electrodes are well known in primary batteries based on the classical Leclanché cell but a more recent development is the introduction of a number of rechargeable redox flow batteries for pilot and commercial scale using a zinc/zinc ion redox couple, in acid or alkaline electrolytes, or transformation of surface zinc oxides as a reversible electrode. The benefits and limitations of zinc negative electrodes are outlined with examples to discuss their thermodynamic and kinetic characteristics along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 236 publications
0
47
0
Order By: Relevance
“…Understanding the performance differences in these two cases helps readers determine if a particular electrode or electrolyte composition is suitable for conventional limited-electrolyte cells, or alternatively, for flow-battery systems that use Zn as an anode material. 22,23 The problem with overstating the impact of results derived from flooded beaker cells without proper context is that such experiments are essentially electrodeposition studies. For example, the ''dendrite problem'' of zinc-based batteries can be approached from many angles including additives to the electrolyte, 24 charging sequence optimization, 25 anode architecture design, [8][9][10] or the literal angle can be 180 , that is ''backside-plating'' as demonstrated by Higashi et al 26 These authors showed, using a flooded cell, that insulating the cathode-facing side of the cell would slow the formation of dendrites because the growing needles would have a more tortuous path when initiating shorts.…”
Section: Cycling Zinc Electrodes: Battery-relevant Testing or Fundamementioning
confidence: 99%
“…Understanding the performance differences in these two cases helps readers determine if a particular electrode or electrolyte composition is suitable for conventional limited-electrolyte cells, or alternatively, for flow-battery systems that use Zn as an anode material. 22,23 The problem with overstating the impact of results derived from flooded beaker cells without proper context is that such experiments are essentially electrodeposition studies. For example, the ''dendrite problem'' of zinc-based batteries can be approached from many angles including additives to the electrolyte, 24 charging sequence optimization, 25 anode architecture design, [8][9][10] or the literal angle can be 180 , that is ''backside-plating'' as demonstrated by Higashi et al 26 These authors showed, using a flooded cell, that insulating the cathode-facing side of the cell would slow the formation of dendrites because the growing needles would have a more tortuous path when initiating shorts.…”
Section: Cycling Zinc Electrodes: Battery-relevant Testing or Fundamementioning
confidence: 99%
“…Similar to the case of the bromine redox couple that exhibits relatively low kinetics, the kinetics of the Ni(OH) 2 /NiOOH couple are inferior as well, which results in the battery working at a comparatively low current density and further lowers its power density. In addition to the kinetics of the nickel couple, the area capacity of commercialized 3D porous nickel foams is limited, and a large area of nickel electrode is required to satisfy the needs of the batteries' high capacity. The large area of the nickel electrode in turn leads to heterogeneous electrochemical reactions for both positive and negative half‐cells during the charge and discharge, which further aggravate the hydrogen and oxygen evolution side reactions of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In addition, zinc is not easily corroded even in alkaline media. [6][7][8][9][10][11][12][13][14] Hence, zincbased batteries commonly have high energy density,l ow cost, high discharge voltage, and good environmental benignity and zinc is one of the most commonlyu sed electrode materials at present.T hese features make zinc-based batteries promising for next-generation energy storage devices. [6][7][8][9][10][11][12][13][14] Hence, zincbased batteries commonly have high energy density,l ow cost, high discharge voltage, and good environmental benignity and zinc is one of the most commonlyu sed electrode materials at present.T hese features make zinc-based batteries promising for next-generation energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…When zinc is used as the electrode material, it also has other positive merits, like high specific energy,h igh powerd ensity,l ow redox potential, nontoxicity,r ecyclability, and low cost. [6][7][8][9][10][11][12][13][14] Hence, zincbased batteries commonly have high energy density,l ow cost, high discharge voltage, and good environmental benignity and zinc is one of the most commonlyu sed electrode materials at present.T hese features make zinc-based batteries promising for next-generation energy storage devices. [4,5,11,12] Notably,a part from pure zinc, zinc oxides,a nd their mixtures can also work as anode materials in zinc-basedbatteries.…”
Section: Introductionmentioning
confidence: 99%